Analiza językowo-kulturowego świata zesłańców syberyjskich na podstawie monografii Eugenii Kucharskiej Sybir w obrazkach - Bator, Oliwia (Wydawnictwo Uniwersytetu Rzeszowskiego, 2024)
The Article consists of an analysis of the linguistic and cultural world of Siberian exiles. The work was prepared on the basis of the monograph Sybir w obrazkach by Professor Eugenia Kucharska, who spent her childhood in distant Kazakhstan. In the description I have adopted the cultural method, which allows to report on the multidirectional aspects of the problems of life in Siberia, and the linguistic method, in which I have taken into account the issue of the interference.
Analysis of the linguistic and cultural world of Siberian exiles based on the monograph by Eugenia Kucharska Sybir w obrazkach
E. Kucharska, Sybir w obrazkach, Szczecin 1998.
Keywords: lexis; Siberia; culture; exile